2015
DOI: 10.1186/s12891-015-0539-9
|View full text |Cite
|
Sign up to set email alerts
|

The trAPP-study: cost-effectiveness of an unsupervised e-health supported neuromuscular training program for the treatment of acute ankle sprains in general practice: design of a randomized controlled trial

Abstract: BackgroundAnkle sprains are one of the most frequent injuries of the musculoskeletal system, with yearly around 680.000 new sprains in the Netherlands. Of these, about 130.000 people will visit the general practitioner (GP) each year. In addition, patients have an increased risk of a recurrent ankle sprain and about a third report at least one re-sprain. No optimal treatment strategy has proven to be effective in general practice, however promising results were achieved in a preventive trial among athletes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Second, because preliminary data for determining the sample size is inadequate, we designed this trial as a single-center pilot study. Third, in previous studies [ 41 44 ], recurrences were followed up for 52 weeks; however, because of the short study duration, we have scheduled a follow-up period of only 26 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Second, because preliminary data for determining the sample size is inadequate, we designed this trial as a single-center pilot study. Third, in previous studies [ 41 44 ], recurrences were followed up for 52 weeks; however, because of the short study duration, we have scheduled a follow-up period of only 26 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately, one third of patients report residual complaints after treatment, such as pain, re-sprain, swelling, muscular weakness, plus loss of function or feelings of instability [ 2 , 6 , 9 , 16 , 19 , 22 , 23 , 40 42 ]. In studies where patients visited their GP after lateral ankle sprain, 47.5% of the patients experienced persistent complaints and only 17.5% regarded themselves as completely recovered [ 9 , 11 , 43 ]. Around 33% of patients experience pain 1 year after spraining an ankle [ 22 , 42 ], and 50% of patients who suffer an ankle sprain experience pain 4 years after suffering the sprain [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, studies with a long-term follow-up, ranging from 5 to 7 years, reported chronic complaints in 20–39% of the patients [ 22 , 45 , 46 ]. In addition to persistent complaints, individuals also have an increased risk of recurrent ankle sprain [ 9 , 41 , 47 ], for example Kreitner, et al [ 48 ] found that up to 34% of patients report at least one re-sprain within 3 years of the initial sprain.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations